X-ray dark-field chest imaging: Qualitative and quantitative results in healthy humans - Gassert, Florian T.; Urban, Theresa; Frank, Manuela; Willer, Konstantin; Noichl, Wolfgang; Buchberger, Philipp; Schick, Rafael; Koehler, Thomas; Von Berg, Jens; Fingerle, Alexander A.; Sauter, Andreas P.; Makowski, Marcus R.; et al. (Radiology, 2021)
Background: X-ray dark-field radiography takes advantage of the wave properties of x-rays, with a relatively high signal in the lungs due to the many air-tissue interfaces in the alveoli. Purpose: To describe the qualitative and quantitative characteristics of x-ray dark-field images in healthy human subjects. Materials and Methods: Between October 2018 and January 2020, patients of legal age who underwent chest CT as part of their diagnostic work-up were screened for study participation. Inclusion criteria were a normal chest CT scan, the ability to consent, and the ability to stand upright without help. Exclusion criteria were pregnancy, serious medical conditions, and changes in the lung tissue, such as those due to cancer, pleural effusion, atelectasis, emphysema, infiltrates, ground-glass opacities, or pneumothorax. Images of study participants were obtained by using a clinical x-ray dark-field prototype, recently constructed and commissioned at the authors’ institution, to simultaneously acquire both attenuation-based and dark-field thorax radiographs. Each subject’s total dark-field signal was correlated with his or her lung volume, and the dark-field coefficient was correlated with age, sex, weight, and height. Results: Overall, 40 subjects were included in this study (average age, 62 years 6 13 [standard deviation]; 26 men, 14 women). Normal human lungs have high signal, while the surrounding osseous structures and soft tissue have very low and no signal, respectively. The average dark-field signal was 2.5 m21 6 0.4 of examined lung tissue. There was a correlation between the total dark-field signal and the lung volume (r = 0.61, P , .001). No difference was found between men and women (P = .78). Also, age (r = -0.18, P = .26), weight (r = 0.24, P = .13), and height (r = 0.01, P = .96) did not influence dark-field signal. Conclusion: This study introduces qualitative and quantitative values for x-ray dark-field imaging in healthy human subjects. The quantitative x-ray dark-field coefficient is independent from demographic subject parameters, emphasizing its potential in diagnostic assessment of the lung.
CRIS-Team Scopus Importer:2023-03-08